OLUŞTURMACI BİLİŞSEL ÇIRAKLIK MODELİNİN YAPI TEKNİĞİ VE UYGULAMASI-I DERSİNDE PSİKOMOTOR ÖĞRENMEYE ETKİSİ - ÇERÇİ, ALİ (Fırat Üniveristesi, 2003)
Araştırmada, gözlem ve değerlendirme formu sonuçlarına göre oluşturmacı öğretim tasarımı sürecinde etkinliklerim gerçekleştiren deney grubu öğrencilerinin kontrol grubundan daha başarılı oldukları sonucuna ulaşılmıştır.Anahtar kelimeler: Oluşturmacılık, bilişsel çıraklık, psikomotor öğrenme, psikomotor beceri, yapı tekniği ve uygulaması

The main aim of this study is to determine the differences between psychomotor perfomances of the students by comparing traditional and constructivist teaching design applications. The treatment was conducted at the Department of Construction Teaching in Technical Education Faculty of Firat University. This experimental research was conducted on 70 students. According to the results of cluster analysis, both experimental and control groups consisted of 35 students. The research design is post test control group design. Tradational teaching design was used in control group. Constructivist cognitive apprenticeship teching design was used in experimental group. The students in the experimental group were taught building production, the behaviours of construction elements before and after earthquake by using cd, application projects and photographs. The control group were taught by using traditional method. Student observation and evaluation form for students' performances was developed in order to measure student' performances in the courses which focused on psychomotor skills mostly. With this form, students' skills on putting up a brick wall by using a l/l brick thickness and plastering on birick wall with lime mortar were evaluated.The students in experimental group were found more successful than thosein control group.Key words : Constructivism, cognitive apperenticeship, psychomotor learning, psychomotor skills, construction technique and application.
The Effects constructivist cognetive apprenticeship model on psychomotor learning in construction tecnique and application-I
Keywords: Eğitim ve Öğretim; Education and Training